Calcium-Mediated Regulation Promotes the Biofilm Formation of Two Novel Pyridine-Degrading Bacteria - Xiong, Fuzhong; Wen, Donghui; Li, Qilin (Frontiers in Environmental Science, 2022)
In bioaugmented wastewater treatment systems, it is essential for recalcitrant pollutant-degrading bacteria to form biofilms. Inducing biofilm formation in these bacteria, however, is challenging as it involves multiple inter-related regulating pathways and environmental factors. Herein, we report the remarkable promoting effect of Ca2+ on biofilm formation of two novel pyridine-degrading bacteria with poor innate biofilm-forming capabilities, Pseudomonas sp. ZX01 and Arthrobacter sp. ZX07. The roles of Ca2+ in different biofilm development stages were investigated. Our data showed strong influences of Ca2+ on the initial attachment of the two strains onto positively charged glass surfaces by altering cell surface charge as well as the cation bridging effect. Contrary to many other biofilm promoting mechanisms, Ca2+ downregulated the extracellular polymeric substances (EPS) production per cell in both Pseudomonas sp. ZX01 and Arthrobacter sp. ZX07, while increasing biofilm biomass. This is attributed to the strong cationic bridging between Ca2+ and EPS which can elevate the efficiency of the extracellular products in binding bacterial cells. Furthermore, Ca2+ increased the protein-to-polysaccharide (PN/PS) ratio in biofilm EPS of both strains, which favored cell aggregation and biofilm establishment by increasing the hydrophobicity of cell surfaces. More intriguingly, the intracellular c-di-GMP, which can drive the switch of bacterial lifestyle from planktonic state to biofilm state, was also elevated markedly by exogenous Ca2+. Taken together, these results would be of guidance for applying the two strains into bioaugmented biofilm reactors where Ca2+ supplement strategy can be employed to facilitate their biofilm formation on the surfaces of engineering carriers.